Prevalencia de bacteriuria asintomática en diabetes tipo 2, con mal control glucémico - Flores Juárez, Eduardo (2004)
In the present investigation it was determined the relationship between the glycosilated hemoglobin, and the prevalence of  asymptomatic bacteriuria. The glycosilated hemoglobin was separeted by cationic interchange resin method and determined by spectrophotometry at 540 nm. For glucemia it was used the enzyme method of glucose oxidase. The bacteriuria was established by carrying out the dired culture in Brolacin and Mc Conkey agar media and the susceptibility by the method of dilution in (Kirby Bauer) agar. The glycosilated hemoglobin from the total of type 2 diabetic patients was 12.0 ± 5.4 % and the control group was 6.0 ± 0.8 % (p > 0.001). The glycemia in the diabetics was 150 ± 78 mg/dl and the control ones was 79.7 ± 11 mg/dl (p > 0.001) From the total of 170 uroculture and antibiogram tests, 90 (53%) was positive with asymplomatic bacteriurea and 80 (47%) was negative. The frequency was 68.9 % of Gram negative germs, 16.6 % of Gram positive germ and 13.3 % of Candida albicans, which differs from obtained results in the non - diabetics with urinary Tract infection. As well as, the Gram negative pathogen agent of grealer incidence was Escherichia colí (38.9%), that showed sensitiveness to Ciprofloxine. From the 90 (53%) diabetic patients with asymptomatic bacteriurea, 39 (43 %) corresponding to the best controlled ( thegood + the acceptable and 51 (57%) to the bad metabolic control ones (>10% of glycosilated hemoglobin). It was found and inverse relationship that is significative between the digits of glycusilated hemoglobin and the prevalence of asymtomatic bacteriuria in the bad controlled diabetic , with regard to the best controlled ones. From above, we can conclude that the asymptomatic bacteriureas in Type 2 diabetes, do not only depends on glycosilation of proteins but other factors and mechanisms that help to appearance of urinary trac infections and metabolic control of glyecmia in the diabetic.